Technical and Financial Studies For Choosing the Right Method pf Coconut Milk Powder Production : Effect of Tween 80 and Soy Milk Concentration - Laksono, S. P.; Kumalaningsih, Sri (Jurnal Teknologi Pertanian, 2000)
The Physico-cemical organoleptic and financial studies of coconut milk powderprocessed by Foam Mat Drying method were carried out. A randomized block designwith two factors namely Tween 80 (0%;  0,4%; and 1%) as the first factor and dry soybean milk concentrations (0%,  2%,  and 5%) a the second factor was used to run thisexperiment. A multiple atribute was applied to select the best treatment for furtherfinancial studies.  The results implied that the best combination treatment was the use of 0,4% Tween80 and 2% dried soy bean milk which produced a promising dried product havingmoisture content of  5,74%; FFA 0,54%; percentage solubility of 85,48%,  Pay  Back Period 3 years and 3 months,  NPV= Rp. 7.910.389; and  IRR = 67,08.Keyword: technical and financial studies, foam mat drying, and soy milk